In situ scanning probe microscopy studies of morphology and growth kinetics in amyloid-peptide fibrillogenesis with custom designed tapping mode and pulsed force mode systems - Hellberg, Magnus; Norlin, Nils; Olevik, David; Almqvist, Nils; Antzutkin, Oleg (Luleå tekniska universitet, Materialvetenskap, 2004)
We have used a commercial Nanoscope II atomic force microscope (AFM) with a custom designedtapping mode (TM) system to in situ monitor amyloid β-peptide aggregation related to Alzheimer’sdisease (AD). The custom tapping mode setup was successfully used to image the real timeaggregation behaviour of the arctic mutation amyloid β-peptide, Aβ(1-40), in vitro in aphysiologically relevant buffer and compare with the behaviour of the normal wild type of theAlzheimer’s amyloid peptide Aβ(1-40) at the same conditions. The investigation revealed distinctdifferences in fibrillogenesis behaviour for the two peptides. Our results demonstrate a previouslysuggested alternative fibrillogenesis pathway, of highly distinct aggregates with orderedmorphology as on-pathway. Moreover, additional investigations using a pulsed force mode (PFM)are under way. Godkänd; 2004; 20120626 (nils)